Report on the first regional training course on the diagnosis on plant pest and disease of food crop held at the faculty of agriculture the University of the West Indies from july 7th-12th, 1986 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2020)
60 páginas.